Kembara ilmu seorang pensyarah fizik : Sungai Semambu ke Monash - Muhamad Yahaya (Kuala Lumpur: Institut Terjemahan & Buku Malaysia, 2020)
Biography of Muhammad Yahaya, a lecturer and physicistsian.
Includes bibliographical references (page 243) and index.
Keywords: Educators -- Malaysia -- Biography; Physics -- Malaysia -- Biography; Autobiography